2002
DOI: 10.1364/ao.41.001012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of Hartmann sensors in strong scintillation

Abstract: A simulation study is presented that evaluates the performance of Hartmann wave-front sensors with measurements obtained with the Fried geometry and the Hutchin geometry. Performance is defined in terms of the Strehl ratio achieved when the estimate of the complex field obtained from reconstruction is used to correct the distorted wave front presented to the wave-front sensor. A series of evaluations is performed to identify the strengths and the weaknesses of Hartmann sensors used in each of the two geometrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 11 publications
0
50
0
Order By: Relevance
“…22 In general, the applications are abundant. 23,24 With wavefront-sensing applications in mind, the presence of deep turbulence tends to be the "Achilles' heel" to modern-day solutions [e.g., the Shack-Hartmann wavefront sensor (WFS), 25 which provides access to localized wavefront slope estimates]. This is said because coherentlight propagation through deep turbulence causes scintillation, which manifests as time-varying constructive and destructive interference between the object and receiver planes.…”
mentioning
confidence: 99%
“…22 In general, the applications are abundant. 23,24 With wavefront-sensing applications in mind, the presence of deep turbulence tends to be the "Achilles' heel" to modern-day solutions [e.g., the Shack-Hartmann wavefront sensor (WFS), 25 which provides access to localized wavefront slope estimates]. This is said because coherentlight propagation through deep turbulence causes scintillation, which manifests as time-varying constructive and destructive interference between the object and receiver planes.…”
mentioning
confidence: 99%
“…Let cx; y be the curl of the vector field ψx; y, i.e., cx; y ∇ y ψ x x; y − ∇ x ψ y x; y; (11) and let ϕx; y, vx; y be the scalar and vector potentials as in Eq. (4).…”
Section: Vector Field Decompositionmentioning
confidence: 99%
“…It is well known that Fried derivatives are good models for Shack-Hartmann sensors, which measure local phase gradients. However, Barchers demonstrated that the Fried geometry performance degrades in high scintillation when compared to Hudgin geometry [11]. When branch points causing phase wrapping are present, it is imperative to properly embed the wrapping operation within the Fried gradients computations.…”
Section: Fried Gradients and Wrapped Fried Gradientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial guess, (0) h , used in the algorithm is a 4x4 block-integrated surface (the x and y-slope maps are combined and locally integrated using the Fried algorithm 8 ) where the shape of each block is determined by integration of the normal data. The center-height of each block is set to the average height over the region as measured by structured light analysis.…”
Section: Final Surface Determinationmentioning
confidence: 99%